Exfoliation of Al-Residual Multilayer MXene Using Tetramethylammonium Bases for Conductive Film Applications - Saita, Emi; Iwata, Masaki; Shibata, Yuki; Matsunaga, Yuki; Suizu, Rie; Awaga, Kunio; Hirotani, Jun; Omachi, Haruka (Frontiers in Chemistry, 2022)
This study describes the concise exfoliation of multilayer Ti3C2Tx MXene containing residual aluminum atoms. Treatment with tetramethylammonium base in a co-solvent of tetrahydrofuran and H2O produced single-layer Ti3C2Tx, which was confirmed via atomic force microscopy observations, with an electrical conductivity 100+ times that of Ti3C2Tx prepared under previously reported conditions. The scanning electrode microscopy and x-ray diffraction measurements showed that the exfoliated single-layer Ti3C2Tx MXenes were reconstructed to assembled large-domain layered films, enabling excellent macroscale electric conductivity. X-ray photoelectron spectroscopy confirmed the complete removal of residual Al atoms and the replacement of surface fluorine atoms with hydroxy groups. Using the exfoliated dispersion, a flexible transparent conductive film was formed and demonstrated in an electrical application.